2022
DOI: 10.21608/ejchem.2022.142955.6242
|View full text |Cite
|
Sign up to set email alerts
|

High -k Green Polymer Nano composites Based on Polyvinyl Alcohol for Electrostatic Dissipation Applications

Abstract: Polyvinyl alcohol (PVA) as a green biodegradable polymeric matrix was chosen to fabricate high-k (high permittivity) polymer nanocomposites with good magnetic and electric properties to be used for electrostatic dissipation applications. PVA was doped with different concentration of magnetite (Fe3O4) nanoparticles and barium titanate (BaTiO3) nanoparticles before and after treatment with ionic liquid (IL). The magnetic properties were investigated by vibrating sample magnetometer (VSM) and the obtained results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The ε 0 and ε 00 values of the PVA-based nanocomposites suggested that they can be used in electrostatic dissipation applications. 19 In addition to these studies, Martis et al tried to develop the optical and dielectric behavior of the PVA by embedding gold nanoparticles in the matrix. As a result of their experimental study, the presence of gold nanoparticles in the PVA matrix reduces the optical band gap energy and enhances both ε 0 and ε 00 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ε 0 and ε 00 values of the PVA-based nanocomposites suggested that they can be used in electrostatic dissipation applications. 19 In addition to these studies, Martis et al tried to develop the optical and dielectric behavior of the PVA by embedding gold nanoparticles in the matrix. As a result of their experimental study, the presence of gold nanoparticles in the PVA matrix reduces the optical band gap energy and enhances both ε 0 and ε 00 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wissa et al doped PVA matrix with Fe 3 O 4 and BaTiO 3 nanoparticles. The 𝜀′ and 𝜀′′ values of the PVA‐based nanocomposites suggested that they can be used in electrostatic dissipation applications 19 . In addition to these studies, Martis et al tried to develop the optical and dielectric behavior of the PVA by embedding gold nanoparticles in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, polymeric binders play another role in pyrotechnic and explosive compositions as it enhances the mechanical performance and provide more protection against environmental condition which increasing shelf life. binder have a vital role for maintain the homogeneity of pyrotechnic mixture and also increasing the safety during pressing process [19][20][21].…”
Section: Introductionmentioning
confidence: 99%